INTERACTIVE DIGITAL CONCEPT MAPS OF IMMUNE SYSTEM TO INCREASE STUDENT INTEREST AND CONCEPTS UNDERSTANDING - Ayu Rahayu; Heru Nurcahyo (BIOEDUKASI, 2020)
The research aims to determine of feasibilty a biology instructional media on the immune system as learning resources and reveal the effect of the developed instructional media on the learning interest and concept understanding of SMA N 1 Godean. This study was a research and development referring to the 4-D Model. The product testing consisted of the Alpha test (media & subject matter expert, biology teachers), and Beta test through two phases, namely small group testing, and large group testing. The data of Alpha and small group testing were analyzed by using the descriptive analysis technique. The large group testing were analyzed by using the t test. The product is in the eligible category as learning resources. The results of the t test show that biology instructional media on the immune system can improve of student learning interest and concept understanding.